Implementasi Standar Nasional Pendidikan pada Sekolah-Sekolah Unggulan di Samarinda - Abdi, Muhammad Iwan; Muri'ah, Siti (FENOMENA, 2017)
Implementation SNP (Education National Standard) in schools in each grade is the minimum criteria that must be met as a measure of achievement in education. One of the positive implications of achievement is the outcome of consistency in implementing the SNP is the emergence of the advantages possessed by the school. The schools’ competition in Samarinda had run to meet the demands of eight educational standards. Excellences that owned by the Madrasah (Islamic Schools) where both of the Madrasah were as a model among many madrasah (Islamic Schools) in Samarinda. The excellences are based on the fulfillment of the standards established in the SNP. These advantages are also implications for the public interest in both of Madrasah to send their children. The schools effort to bring school-superiority in terms of educating the students on aspects of cognitive, affective and psychomotor by presenting models of learning that are innovative, creative and fun. In addition, the schools have also implemented a school-based management model (SBM). School strategies in planning, implementation, and evaluation for the attainment of the eight standard of SNP are by involving various parties through school committee and stakeholders that are considered competent in fulfill the needs of the development of madrasah